Knowledge of risk factors and preventive measures of Hepatitis B and Hepatitis C among Health care workers at Bolan Medical Complex Hospital, Quetta. - Waheeda Baloch; Irshad Ahmed; Abdul Bari; Sunil Kumar; Azmatullah; Muhammad Ibrahim (International Journal of Endorsing Health Science Research, 2023)
Background: This study aimed to determine the frequency of adequate knowledge regarding risk factors and preventive measures of Hepatitis B and C among healthcare workers (HCWs) at Bolan Medical Complex Hospital, Quetta. Methodology: A cross-sectional study of 141 participants was conducted at Bolan Medical Complex Hospital, Quetta, after obtaining approval from the ethical review board of Bolan Medical Complex Hospital, Quetta. The sample size was calculated, keeping the prevalence of adequate knowledge of risk factors and preventive measures of Hepatitis B and Hepatitis C among healthcare workers at 62.5%, the margin of error d=8%, and 95% confidence level. The study continued from 1st January to 31st June 2016. All healthcare workers between 25 to 60 years of age, working in a hospital for more than six months, were included in the study. While all the non-consenting participants, those with anti-HCV and HBsAg positive analyzed via ELIZA methods, were kept in the exclusion criteria. The enrolled healthcare workers were interviewed, and knowledge of hepatitis risk factors and preventive measures was assessed using a 10-item structured self-administered questionnaire. The data were analyzed using SPSS version 19.0. Results: The mean age of the study participants was 33.16 ± 8.31 years. The majority were female (69.50%) and > 40 years old (70.92%). Most of the enrolled healthcare workers were doctors (61.70%). The mean service duration was 7.85 ± 9.10 years. Out of 141 HCWs, 71(50.35%) had adequate knowledge of risk factors and preventive measures for Hepatitis B and C. Doctors had significantly more adequate knowledge than staff nurses (76.05% vs. 23.94%; p=0.000). Moreover, those with more formal educational years had significantly adequate knowledge of Hepatitis B and C risk factors and preventive measures than those with lesser educational years (p<0.05). Conclusion: According to the survey findings, there is an adequate level of knowledge among the enrolled HCWs.